EARLY DETECTION AND SELF MONITORING OF COVID-19 STATUS THROUGH ELECTRONIC BASED SURVEILLANCE IN KENJERAN SUB-DISTRICT, BULAK DISTRICT, SURABAYA - Arief Hargono; Santi Martini; Kurnia Dwi Artanti; Erren Silvia (Jurnal Pengabdian Masyarakat Dalam Kesehatan, 2021)
Introduction: Data from the Ministry of Health of the Republic of Indonesia shows that confirmed Covid-19 cases in Indonesia as of November 29, 2020, have reached 534,266 cases with 16,815 deaths. This figure is an increase compared to the previous report. The implementation of surveillance needs to be supported by information technology to speed up the process of recording, reporting, and analyzing data. The socialization of Covid-19 surveillance among residents of Kenjeran sub-district, Bulak district, Surabaya city has a significant impact on increasing participants' knowledge about Covid-19 surveillance.Methods: The method used in this activity was the socialization and training of the Covid-19 surveillance application for the community. The assessment was carried out to determine the acceptance of the Covid-19 surveillance application information technology through in-depth interviews with a number of training participants via telephone a few days after the training. The assessment is carried out by asking 10 questions consisting of conditions that facilitate, application function, ease of use of the application, and desire to use the application.Results: The results of testing the application of the Covid-19 surveillance application in the community showed that this application was able to perform its function as data input and produce information about the status of Covid-19 and its recommendations quickly.Conclusion: The results of testing the application of the Covid-19 surveillance application in the community indicate that this application is able to perform its function as data input and produce information about the status of Covid-19 and its recommendations quickly. There were obstacles when registering participants, but participants had the desire to continue to use the Covid-19 surveillance application because it was very helpful in determining the status of Covid-19 quickly and accurately.